Accidente ofídico por Bothrops barnetti. Apropósito de un caso - Vargas Vásquez, Nohiver (2025)
Bothropic accidents caused by Bothrops barnetti, are relatively common in the northern Peruvian highlands, and they are associated with complications such as secondary coagulopathy, vascular toxicity, and nephrotoxicity. We present the case of a 35-year-old male patient from the northern Peruvian highlands (Piura region) who suffered a bothropic accident. He developed multiple organ damage and was admitted to the Intensive Care Unit of Las Mercedes Hospital in Chiclayo.